Flood tolerance in two tree species that inhabit both the Amazonian floodplain and the dry Cerrado savanna of Brazil - Pires, Hérica Ribeiro Almeida (AoB Plants, 2018)
Comparing plants of the same species thriving in flooded and non-flooded ecosystems helps to clarify the interplay between natural selection, phenotypic plasticity and stress adaptation. We focussed on responses of seeds and seedlings of Genipa americana and Guazuma ulmifolia to substrate waterlogging or total submergence. Both species are commonly found in floodplain forests of Central Amazonia and in seasonally dry savannas of Central Brazil (Cerrado). Although seeds of Amazonian and Cerrado G. americana were similar in size, the germination percentage of Cerrado seeds was decreased by submergence (3 cm water) and increased in Amazonian seeds. The seeds of Amazonian G. ulmifolia were heavier than Cerrado seeds, but germination of both types was unaffected by submergence. Three-month-old Amazonian and Cerrado seedlings of both species survived 30 days of waterlogging or submersion despite suffering significant inhibition in biomass especially if submerged. Shoot elongation was also arrested. Submersion triggered chlorosis and leaf abscission in Amazonian and Cerrado G. ulmifolia while waterlogging did so only in Cerrado seedlings. During 30 days of re-exposure to non-flooded conditions, G. ulmifolia plants that lost their leaves produced a replacement flush. However, they attained only half the plant dry mass of non-flooded plants. Both submerged and waterlogged G. americana retained their leaves. Consequently, plant dry mass after 30 days recovery was less depressed by these stresses than in G. ulmifolia. Small amounts of cortical aerenchyma were found in roots 2 cm from the tip of well-drained plants. The amount was increased by flooding. Waterlogging but not submergence promoted hypertrophy of lenticels at the stem base of both species and adventitious rooting in G. ulmifolia. Despite some loss of performance in dryland plants, flood tolerance traits were present in wetland and dryland populations of both species. They are part of an overall stress-response potential that permits flexible acclimation to locally flooded conditions.